The Role of Psychologists, Social Specialists, and Health Experts in Improving Mental and Physical Health Outcomes - Faisal Awwadh Alotaibi; Malaa Abdullah Alotaibi; Majed Faris Alotaibi; Ahmad Saeed Alotaibi; Abdullah Muslat Alsubaie; Yasser Salem Alshehri; Faisal Saeed Althobaiti; Marzouq Bakheet Almayhubi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Today, in the context of contemporary healthcare, it is of immense importance to bring together the mental, social, and medical science in order to elucidate the intricate relationship between the mental and physical health. The approach provides such a comprehensive view that recognizes that mental and physical well-being cannot be divorced or separated, so taking efforts in this direction would be best done in collaboration with the psychologists, the social specialists, and the health experts. Aim of work: Toexploremultifaceted roles these professionals play in enhancing health outcomes. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Role, Psychologists, Social Specialists, Health Experts, Improving, Mental, Physical and Health Outcomes. The search was restricted to publications from 2016to 2025 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2025. The study was structured into various sections with specific headings in the discussion section. Conclusion:Psychologists, social specialists, and health experts have direct roles in bringing about mental and physical health outcomes. Yet work of these various professionals can be done through collaboration and in a holistic manner to provide for the different needs of patients. When they acknowledge that the mental and physical are part of the same whole, and can work collectively to provide complete care to the people in the community and those people in the community can live a much better life.